Effect of Some Salts on the Soil Reaction and Growth and Dry Matter Yield of Leucaena leucocephala and Acacia auriculiformis in Pot Culture - Prasad, Arun; Totey, N. G.; Kapoor, K. S.; Khatri, P. K.; Chouhan, J. S.; Bhowmik, A. K. (Indian Forester, 1990)
A pot experiment as conducted to study the effect of some salts on the soli reaction and the growth and dry matter yield of Leucaena leucocephala and Acacia auriculiformis. Addition of FeSO4 slightly decreased the soil pH whereas CaCO3 and Na2CO3 increased it. Application of FeSO4 decreased the plant height. In case of Leucaena leucocephala more at earlier stage whereas it increased the height of Acacia auriculiformis. Addition of CaCo3, decreased the height of both the species. The application of CaCO3, along with Na2CO3 had seriously affected the growth and survival of these two species.The dry matter yield of both the species was enhanced with the addition of FeSO4. The application of CaCO3 @ 10g/kg soil, increased the dry matter yield of Leucaena leucocephala whereas the yield of Acacia auriculiformis remained alomost unaffected. Further increase in the level of CaCO3 applied alone or with Na2CO3 reduced the dry matter yield of both the species. Added FeSO4 and CaCO3 at lower dose, increased the dry weight of root nodules and further increase in the level of CaCO3 decreased the nodule weight.